The primary carbon metabolism in cyanobacteria and its regulation - Lucius, Stefan; Hagemann, Martin (Frontiers in Plant Science, 2024)
Cyanobacteria are the only prokaryotes capable of performing oxygenic photosynthesis. Many cyanobacterial strains can live in different trophic modes, ranging from photoautotrophic and heterotrophic to mixotrophic growth. However, the regulatory mechanisms allowing a flexible switch between these lifestyles are poorly understood. As anabolic fixation of CO2 in the Calvin-Benson-Bassham (CBB) cycle and catabolic sugar-degradation pathways share intermediates and enzymatic capacity, a tight regulatory network is required to enable simultaneous opposed metabolic fluxes. The Entner-Doudoroff (ED) pathway was recently predicted as one glycolytic route, which cooperates with other pathways in glycogen breakdown. Despite low carbon flux through the ED pathway, metabolite analyses of mutants deficient in the ED pathway revealed a distinct phenotype pointing at a strong regulatory impact of this route. The small Cp12 protein downregulates the CBB cycle in darkness by inhibiting phosphoribulokinase and glyceraldehyde 3-phosphate dehydrogenase. New results of metabolomic and redox level analyses on strains with Cp12 variants extend the known role of Cp12 regulation towards the acclimation to external glucose supply under diurnal conditions as well as to fluctuations in CO2 levels in the light. Moreover, carbon and nitrogen metabolism are closely linked to maintain an essential C/N homeostasis. The small protein PirC was shown to be an important regulator of phosphoglycerate mutase, which identified this enzyme as central branching point for carbon allocation from CBB cycle towards lower glycolysis. Altered metabolite levels in the mutant ΔpirC during nitrogen starvation experiments confirm this regulatory mechanism.The elucidation of novel mechanisms regulating carbon allocation at crucial metabolic branching points could identify ways for targeted redirection of carbon flow towards desired compounds, and thus help to further establish cyanobacteria as green cell factories for biotechnological applications with concurrent utilization of sunlight and CO2.